Exploring Secure High-Performance Container Network Mesh Solutions - Ramasankar Molleti (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This study examines and comprises analyses of various aspects of the secure high-performance container network mesh solutions in response to the container and microservices architecture. It looks at the historical development of these solutions, basic ingredients, and today’s specifics of both open-source and commercial solutions. The focus of the study falls on the key security issues and their solutions as well as the performance. It provides information on how these can be done through case studies and benchmarks to show current practical implementations and performance comparisons. The study also identifies the future trends and research directions of this dynamic area of study. The results emphasize that security is of high value in container network meshes, also, performance and complexity should be optimal in the solutions. This study enhances the knowledge of today’s potential and tomorrow’s possibilities of these solutions and will be useful for researchers, practitioners, and decision-makers involved in containerized application deployment and management. DOI: https://doi.org/10.17762/ijisae.v11i4.6724